PASsing on Signals: PAS Kinase (PASK)-mTOR Signaling Conveys Nutrient Sufficiency Signals to Epigenetic (COMPASS) Complexes to Activate Stem Cell Differentiation Program (P15-009-19). (13th June 2019) - Kikani, Chintan; Xiao, Michael; Wu, Xiaoying; Rutter, Jared
Abstract: Objectives: To determine how nutrient signaling impacts stem cell functions Methods: PASK phosphorylation: We measured in situ phosphorylation of PASK by metabolic 32P labeling of stem cells expressing WT or mutant versions of PASK. PASK Activation: PASK activation was measured using in vitro kinase assay using radio-labeled ATP. Myogenesis: Myogenesis was measured by immunohistological, and immunofluorescent analysis of differentiating muscle stem cells. Antibodies used were: Myogenin (F5D-Developmental Hybridoma), MF20 (Myosin heavy chain), Pax7 and MyoD. Results: Stem cell fate in the tissue niche is intimately connected with intracellular metabolic state and the extracellular hormonal stimulations. We have identified PAS domain containing K inase (PASK) as a stem cell enriched protein kinase that is required for establishment of the differentiation program in many stem cell paradigms. For this function, PASK phosphorylates Wdr5, a member of the COMPASS family of histone methyltransferases, to activate the epigenetic processes required for the stem cell differentiation (eLife, 2016). Here we show that a master nutrient sensor, mTOR complex 1 (mTORC1) activates PASK via multi-site phosphorylation during stem cell differentiation. This phosphorylation of PASK by mTORC1 is required for epigenetic activation of the Myogenin transcription, exit from the self-renewal and induction of the myogenesis program. Our data suggest that mTORC1-PASK signaling generates MyoG + committed myoblasts (epigenetically - an early stage of myogenesis), whereas mTORC1-S6K1 signaling is required for myoblast fusion (translationally - later stage of myogenesis). Conclusions: Our discoveries show that nutrient signaling can partition stem cell fates during different stages of the myogenesis program downstream of mTOR signaling via activation of two distinct protein kinases. Funding Sources: NIH R01 (Chintan Kikani), HHMI (Jared Rutter) Supporting Tables, Images and/or Graphs: